Fast track to personalized TCR T cell therapies - Levy, Pierre L; Gros, Alena (Cancer cell, 2022)
In this issue of Cancer Cell, Hanada et al. leverage single-cell multi-omics of lung cancer resident lymphocytes to identify phenotypic and transcriptomic signatures differentially expressed by neoantigen-reactive clonotypes. These findings could substantially expedite the selection of neoantigen-specific T cell receptors (TCRs) for individualized T cell therapies.